2016
DOI: 10.4137/ebo.s40152
|View full text |Cite
|
Sign up to set email alerts
|

Genomics Study of Mycobacterium tuberculosis Strains from Different Ethnic Populations in Taiwan

Abstract: To better understand the transmission and evolution of Mycobacterium tuberculosis (MTB) in Taiwan, six different MTB isolates (representatives of the Beijing ancient sublineage, Beijing modern sublineage, Haarlem, East-African Indian, T1, and Latin-American Mediterranean (LAM)) were characterized and their genomes were sequenced. Discriminating among large sequence polymorphisms (LSPs) that occur once versus those that occur repeatedly in a genomic region may help to elucidate the biological roles of LSPs and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…This is inconsistent with the conclusion that subtype A is the dominant strain in human 52,53 . It may be that the hMPV dominant strain is different in different populations, or that our experiment time is too short 54,55 . In a word, our experiments showed that the competition exist between the two subtypes and this competition could affect the alternation of genotype prevalence.…”
Section: Discussionmentioning
confidence: 99%
“…This is inconsistent with the conclusion that subtype A is the dominant strain in human 52,53 . It may be that the hMPV dominant strain is different in different populations, or that our experiment time is too short 54,55 . In a word, our experiments showed that the competition exist between the two subtypes and this competition could affect the alternation of genotype prevalence.…”
Section: Discussionmentioning
confidence: 99%
“…After performing the de-multiplexing procedure, the average sequence size of each sample was 3.38 Gb, and the depths of these samples ranged from 568- to 1068-fold when mapped to the H37Rv reference sequence, resulting in a reference coverage of these samples of 99.44% to 99.82%. The detailed information was described in our recent article 29 .…”
Section: Methodsmentioning
confidence: 99%